PENGARUH AKTIVITAS DALAM ORGANISASI KEMAHASISWAAN TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Nelly Lestari; Gimin '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT: This study aims to determine the effect of activities in student organizations on learning outcomes. The method used in this research is quantitative descriptive, then the data is tabulated and analyzed using SPSS program. Population in this research are student of class of 2013, 2014, and 2015 FKIP University of Riau Economic Education as many as 52 respondents, and samples taken by census. The research instrument used is questionnaire and documentation. The data analysis used is simple linear regression. The result of the research shows that the activity in student organization affects the students' achievement of FKIP University Economic Education. Based on the result of descriptive analysis, the activity in student organization is quite active as much as 32 students (61,54%), and the result of study that follow student organization is not good enough 2,65-2,96 counted 20 student (38,46%). From the results of simple linear regression analysis obtained constanta value (a) of 4.585 and the value of regression coefficient (b) of 0.019 with regression equation Y = 4,585 - 0,019X. From the results of simple linear regression analysis, there is a negative influence between the activities in student organizations on learning outcomes, it can be concluded that the more activities in student organizations that followed will decrease the learning outcomes. Judging from the calculation of R2 (R Square Change) obtained value of 0.380. It means that the contribution of activity in student organization to learning result is 38%.Keywords: Activities, Student Organization, Learning Outcomes